Reward Satisfaction as a Driver of Employee Performance at Toraja Indonesian Christian University - Tangdialla, Randi; Pasoloran, Octavianus; Marewa, Jens Batara; Pelu, Jeri (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2024)
This study aims to analyze and determine the role of satisfaction with rewards (financial reward satisfaction, material reward satisfaction, psychological reward satisfaction) on the performance of lecturers and employees at UKI Toraja. The data collection procedures for this study are observation, interviews, questionnaires, and literature studies. The method used in this study is a quantitative method using multiple linear regression and processed using SPSS. This study was conducted on lecturers and employees of UKI Toraja with a sample of 76 respondents. The results of the study revealed that the three dimensions of rewards, namely FRS, MRS and PRS, can improve performance. This indicates that when someone feels satisfied with financial and non-financial rewards, it will have an impact on improving performance. The role of management is very much needed in this case to integrate the dimensions of rewards so that employee performance can be achieved optimally.